5+5z-3=8z+20-6z

Simple and best practice solution for 5+5z-3=8z+20-6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+5z-3=8z+20-6z equation:


Simplifying
5 + 5z + -3 = 8z + 20 + -6z

Reorder the terms:
5 + -3 + 5z = 8z + 20 + -6z

Combine like terms: 5 + -3 = 2
2 + 5z = 8z + 20 + -6z

Reorder the terms:
2 + 5z = 20 + 8z + -6z

Combine like terms: 8z + -6z = 2z
2 + 5z = 20 + 2z

Solving
2 + 5z = 20 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
2 + 5z + -2z = 20 + 2z + -2z

Combine like terms: 5z + -2z = 3z
2 + 3z = 20 + 2z + -2z

Combine like terms: 2z + -2z = 0
2 + 3z = 20 + 0
2 + 3z = 20

Add '-2' to each side of the equation.
2 + -2 + 3z = 20 + -2

Combine like terms: 2 + -2 = 0
0 + 3z = 20 + -2
3z = 20 + -2

Combine like terms: 20 + -2 = 18
3z = 18

Divide each side by '3'.
z = 6

Simplifying
z = 6

See similar equations:

| 7-4x=-6x+17 | | 1.6x=128 | | 15=7/10g-44.5 | | 3-5x=3/10x+5 | | -7x-10=4x+12 | | x-3+7=11 | | 3.4km+16k= | | -2(-6)-2= | | 84=12(x+3) | | 3y^4-8y^2+5z^2= | | [(3-5)-(1-6)-2]-[(4-3)-2(-3)]= | | 9x=63+2x | | 7x+14=2(x+2) | | 9x+18x=189 | | 21m-35= | | 103=23-8x | | 4x+2(3x+8)=6 | | 20z+30yz= | | -3x^2+6x-1=y | | 1/7(4x-14) | | 16y-12= | | -22=11c(2c+8) | | Y=25-6x | | -7.4x=66.6 | | 1/3+2/3x+3/4=21/12 | | 7(4+k)=42 | | 5y+2=-4+3y | | 5(4x+3)+3(4y+1)=66 | | 3x+3.1=9.4 | | e-24= | | 8x-6=-46 | | -1.5=0.5-2x |

Equations solver categories